(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
This study evaluates public exposure to and awareness of toxic metal and pesticide contamination in paddy fields, and examines attitudes toward paying a premium for safe rice. It also explores rice consumption patterns and sources to inform stakeholders such as farmers, policymakers, and marketers. Data were collected through a semi-structured questionnaire administered to 600 respondents across four rice-producing communities in Nigeria: Igbemo (Ekiti), Pategi (Kwara), Isoku (Ogun), and Akeke (Edo). The study used both close-ended and open-ended questions to capture detailed responses about public health risks related to pesticide and heavy metal contamination. Descriptive statistics and binary regression analysis were employed to analyze the data. The findings reveal that most Nigerians prefer locally grown rice, which they consume regularly or occasionally. About 13% of respondents reported chemical exposure from paddy fields via their diet, and 12-13.9% experienced health problems linked to contaminated rice. Approximately 36.6% were aware of pesticide and heavy metal contamination in their area. Those aware of mitigation efforts were 14.9 times more willing to pay a premium for safe rice (B = .879, X2 = 14.901; p < 0.05). Educational initiatives were identified as the most effective strategy to reduce contamination, with 44.1% of respondents supporting this approach. Improving agricultural practices (24.3%) and enforcing regulatory standards (23.4%) were also deemed important, while 8.3% favored promoting diverse rice varieties. These results underscore the need for enhanced public education, improved agricultural methods, and stricter regulations to ensure rice safety and sustainability.